Inflammatory Markers in Substance Use and Mood Disorders: A Neuroimaging Perspective - Agarwal, Khushbu; Manza, Peter; Chapman, Marquis; Nawal, Nafisa; Biesecker, Erin; McPherson, Katherine; Dennis, Evan; Johnson, Allison; Volkow, Nora D.; Joseph, Paule V. (Frontiers in Psychiatry, 2022)
Chronic exposure to addictive drugs in substance use disorders and stressors in mood disorders render the brain more vulnerable to inflammation. Inflammation in the brain, or neuroinflammation, is characterized by gliosis, microglial activation, and sustained release of cytokines, chemokines, and pro-inflammatory factors compromising the permeability of the blood-brain barrier. There is increased curiosity in understanding how substance misuse and/or repeated stress exposure affect inflammation and contribute to abnormal neuronal activity, altered neuroplasticity, and impaired cognitive control, which eventually promote compulsive drug-use behaviors and worsen mood disorders. This review will emphasize human imaging studies to explore the link between brain function and peripheral markers of inflammation in substance use disorders and mood disorders.